Monopterus ichthyophoides, a new species of scaled swamp eel (Teleostei: Synbranchiformes: Synbranchidae) from Mizoram, India - Britz, Ralf; Lalremsanga, Hmar Tlawmte; _, Lalrotluanga; _, Lalramliana (Zootaxa, 2011)
Monopterus ichthyophoides is described from specimens collected from the Sawleng River and a public well at Luangmual, both in the Barak River drainage in Mizoram, India. The new species differs from all other synbranchids in having only two, instead of five or six branchiostegal rays. It belongs to the Amphipnous species group characterized by possession of scales on the body and can be readily distinguished from all other species of this group by the lower number of vertebrae (114–117 vs 126–188).